PENGARUH MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA CV. MANDIRI PHOTO CABANG KEBAYORAN LAMA JAKARTA SELATAN - Rafly Ramadhani; Henni Marlinah (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of work motivation and organizational culture, both partially and simultaneously, on employee performance at CV. Mandiri Photo Kebayoran Lama Branch, South Jakarta with a sample of 52 employees. The method used is a quantitative method. The data analysis used in this research is the classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and F test. The results of this research are that work motivation has a significant effect on employee performance in the Y regression = 17,100 + 0.721 Organizational culture has a significant effect on employee performance with the regression equation Y = 3,821 + 0.905 Work motivation and organizational culture simultaneously have a significant effect on employee performance with the regression equation Y = 3,888 + 0.359 X1 + 0.623 X2. The coefficient of determination value is 72%, while the remaining 18% is caused by other variables not examined in this research. The test results for the first hypothesis obtained a calculated t value > t table or (7,880 > 2,008). Based on the results of testing the second hypothesis, the calculated t value > t table or (3.821 > 1.670) is obtained. Based on the results of testing the third hypothesis, the calculated F value was 62,883 > F table 3,190. This shows that simultaneously the variables of work motivation and organizational culture have a significant influence on employee performance.